Alternative weir design using circular crested type and vlughter type energy dissipators on the Yeh Empas Longstorage in Tabanan Regency - I Dewa Ayu Mega Swari; Cok Agung Yujana; Ni Made Widya Pratiwi; Putu Aryastana (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2023)
Climate change affects seasonal changes throughout the world, including in Indonesia a tropical country that experiences rainy and dry seasons with the possibility of facing drought or flood disasters. The long storage construction has an objective to overcome the problem of water availability during the dry and rainy seasons. The Yeh Empas long storage is one of the construction weirs with rubber as a barrier and a movable gate in the Yeh Empas River as a reservoir for raw water for Tabanan Regency. The utilization of movable gates and rubber weir bodies has disadvantages in terms of cost and construction time due to the ordering time. The objective of the current study is to design an alternative weir using circular crested type and Vlughter type energy dissipators without replacing the long storage function. The weir was designed by implementing a 100-year return period flood discharge of 163.29 m3/dt. The design result depicts the dimensions of weir elements consisting of the crest radius, the crest height, the energy dissipator length, the upstream slope, the downstream slope, and the effective width is 1.00 m, 3.30 m, 5.70 m, 2:3, 1:1, and 26.31 m, respectively.